2011
DOI: 10.1186/1471-2407-11-157
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel lymph node biopsy as guidance for radical trachelectomy in young patients with early stage cervical cancer

Abstract: BackgroundThe purpose of this study was to assess the feasibility and accuracy of sentinel lymph nodes (SLNs) detection using 99mTc phytate in predicting pelvic lymph nodes status for radical abdominal trachelectomy (RAT) in patients with early stage cervical cancer.MethodsSixty-eight women with stage IA2-IB1 cervical cancer and scheduled to undergo fertility-sparing surgery enrolled in this study. 99mTc-labeled phytate was injected before surgery. Intraoperatively, SLNs were identified, excised, and submitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
1
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(44 citation statements)
references
References 26 publications
1
39
1
3
Order By: Relevance
“…[1517] Though radiation doses are variable based upon which protocol is used, overall radiation exposure remains small. Intracervical injection techniques are similar to those described for blue dye.…”
Section: Mapping Techniquesmentioning
confidence: 99%
See 2 more Smart Citations
“…[1517] Though radiation doses are variable based upon which protocol is used, overall radiation exposure remains small. Intracervical injection techniques are similar to those described for blue dye.…”
Section: Mapping Techniquesmentioning
confidence: 99%
“…Many published studies utilize a “long” protocol, whereby the tracer is injected intracervically the day prior to surgery. [15, 17, 19, 20] In these studies, preoperative imaging with lymphoscintigraphy or SPECT-CT is performed so that the surgeon will have this information ahead of proceeding to the operating room. If the isotope is injected less than 24 hours from surgery, reinjection is often unnecessary as the half-life of isotope is approximately 6 hours.…”
Section: Mapping Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…fertility-sparing treatment [5]. Furthermore, detection of nodal metastasis is potentially improved by pathologic ultrastaging, which includes multiple serial sectioning and immunohistochemical assessment of the SN.…”
mentioning
confidence: 99%
“…Large studies in early-stage cervical cancer patients using radiocolloid tracers reported higher detection rates varying from 88% to 99% (17)(18)(19)(20)(21)(22)(23). Possible explanations for the lower detection rate observed in this study could be the inclusions of patients with larger tumors (>2 cm) and, especially, the learning curve associated with cervical injection of the tracer and the intraoperatively exposure of tissue to maximize NIR fluorescence detection (17;24).…”
Section: Discussionmentioning
confidence: 73%